Respuesta :
A
p/s : follow me and I will help you more about maths :))))
![Ver imagen gazatavnp5viw6](https://us-static.z-dn.net/files/d1e/52811d823bb7fe0cdb0ec340d4752e4b.jpg)
Answer:
Option 1 is correct.
Step-by-step explanation:
Given the expression
[tex]sin^4x=\frac{1}{8}{(3-4cos2x+cos4x)}[/tex]
we have to complete the fourth step to prove the above result.
[tex]sin^4x=(sin^2x)^2\\\\sin^4x=(\frac{1-cos2x}{2})^2 \\\\sin^4x=\frac{1-2cos2x+cos^22x}{4}[/tex]
As, [tex]cos^2x=\frac{1+cos2x}{2}[/tex]
⇒ [tex]cos^{2}2x=\frac{1+cos4x}{2}[/tex]
Hence, the next step becomes
[tex]sin^4x=\frac{1-2cos2x+\frac{1+cos4x}{2}}{4}[/tex]
Hence, option 1 is correct.